An efficient approach to mitigate scintillation effects on GPS range-finding in ionosphere - Abdul Rahman, Farah Diyana; Hassan Abdalla Hashim, Aisha; Strangeways, Hal (Faculty of Engineering, International Islamic University Malaysia, 2008)
This paper presents the optimal approach to mitigate scintillation effects caused by ionosphere irregularities, principally plasma bubbles that occur mostly in ionosphere in low latitude. The mitigation is made by figuring out the scintillation index for the chosen geographic location, extracted from the received real-time RINEX data. Various simulators and programs are used, mainly MATLAB, such as Transionospheric Simulator, Scintillation Index Simulation Program, Power Spectral Density Program, Read RINEX Observation Program and Bubble Scintillation Simulation Program. Based on the detrend signal, MATLAB function that is polyfit will be used to find the phase and amplitude spectra. Comparison simulations result with Bubble Scintillation Simulation Program, which is programmed to detect plasma bubbles in certain geographical area under ob servations, is executed. The result of this study will provide information for ionospheric activity and also enable GPS system to make predictions and necessary adjustments to maximize its navigations.